Enhancing Percut Watershed sustainability in North Sumatra: the role of monitoring and evaluation - Rahmawaty; Rauf, Abdul; Nugroho, Sigit Budi; Isdhiartanto, Era; Sitakar, Binti Ma’niyah; Barus, Sriyanti Puspita; Harahap, Fitra Syawal; Salleh, Siti Aekbal; Ismail, Mohd Hasmadi (National University of Malaysia, 2026)
The Percut Watershed is vital in supporting the region’s ecological and socio-economic systems. However, the watershed has been increasingly impacted by rapid urbanization, deforestation, pollution, and unregulated land use, leading to environmental degradation and decreased water quality. This study aims to assess the current state of the Percut Watershed and evaluate the effectiveness of ongoing management practices. The research utilizes a combination of water quality analysis, land-use mapping through Geographic Information Systems (GIS), and stakeholder engagement to monitor key environmental indicators. The research results show that the Percut Watershed has a restored classification where the total value of the watershed carrying capacity reaches 101.75 (including the “moderate” criteria). Criteria that need attention are critical land and flood vulnerability. The land parameters in the Percut Watershed are considered quite good, with the erosion index in the Percut Watershed also having a moderate value; this is because, apart from natural topographic factors, there is also a mismatch in land use with existing land capabilities. The condition of the water system in the Percut Watershed is considered quite good because the flow regime coefficient value is low, which indicates the land’s ability to hold and store water is quite good high annual flow coefficient value. The use of regional space in the Percut Watershed is still good. Attention needs to be paid, especially to cultivated areas that are topographically less suitable for agricultural cultivation. Effective monitoring and evaluation are crucial for addressing these challenges and ensuring the sustainable management of the watershed.